The Role of Metacognitive Instruction through Pedagogical Cycle on Metacognitive Awareness of EFL Learners: Gender Difference Focus - hossein bozorgian; Bita Padiav (Journal of Modern Research in English Language Studies)
Listening comprehension has always been a challenge for English as Second/Foreign Language (ESL/EFL) learners, in general. Therefore, the purpose of this study is particularly to investigate the role of metacognitive instruction through pedagogical cycle on the metacognitive awareness of EFL learners across genders. The participants in this study were 83 Iranian intermediate learners in four groups (two male and two female groups) chosen randomly out of 97 available EFL learners, ranging from 20 to 29 years old. The learners in the experimental groups (N = 60) were trained based on metacognitive instruction through pedagogical cycle for ten weeks over a semester, and participated in EFL listening tasks. However, the learners in the control groups (N = 23) underwent conventional instruction of listening strategies. All four groups were taught by the same teacher and listened to the same materials. The Metacognitive Awareness of Listening Question (MALQ) was used to collect data and to track changes in metacognitive awareness of learners across the genders before and after the intervention. The finding indicates that the experimental group outweighed the control group in terms of metacognitive awareness, but gender did not have any effect on metacognitive awareness of learners.